Implementasi Dynamic Difficulty Adjustment pada Racing Game Menggunakan Metode Behaviour Tree - Isthofi Aslim Sofyan; Muhammad Aminul Akbar; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Video games is all about entertainment and challenge. Without challenge video games will be too easy and boring. But if the challenge is too hard it can make the player frustrated and give up. This related to flow-state where the goal is to find balance between player skills and game challenge. In general, almost every game has difficulty level settings. The difficulty usually ranged from easy, medium, to hard. Unfortunately, this type of difficulty is static, giving inequalities between players and AI. To solve this problem Dynamic Difficulty Adjustment is applied in this research. By applying DDA the difficulty of the game will automatically adjusts to player's ability as the game progress. To support DDA implementation, Behavior Tree is used to help AI to adapt to player's ability. By implementing both method, the game used in this research become less boring and challenging for player.